Upper limb joint muscle/tendon injury and anthropometric adaptations in French competitive tennis players - Rogowski, I.; Creveaux, T.; Genevois, C.; Klouche, S.; Rahme, M.; Hardy, P. (European Journal of Sport Science, 2016)
The purpose of this study was to examine the relationship between the upper limb anthropometric dimensions and a history of dominant upper limb injury in tennis players. Dominant and non-dominant wrist, forearm, elbow and arm circumferences, along with a history of dominant upper limb injuries, were assessed in 147 male and female players, assigned to four groups based on location of injury: wrist (n = 9), elbow (n = 25), shoulder (n = 14) and healthy players (n = 99). From anthropometric dimensions, bilateral differences in circumferences and in proportions were calculated. The wrist group presented a significant bilateral difference in arm circumference, and asymmetrical bilateral proportions between wrist and forearm, as well as between elbow and arm, compared to the healthy group (6.6 ± 3.1% vs. 4.9 ± 4.0%, P < 0.01; -3.6 ± 3.0% vs. -0.9 ± 2.9%, P < 0.05; and -2.2 ± 2.2% vs. 0.1 ± 3.4%, P < 0.05, respectively). The elbow group displayed asymmetrical bilateral proportions between forearm and arm compared to the healthy group (-0.4 ± 4.3% vs. 1.5 ± 4.0%, P < 0.01). The shoulder group showed significant bilateral difference in elbow circumference, and asymmetrical bilateral proportions between forearm and elbow when compared to the healthy group (5.8 ± 4.7% vs. 3.1 ± 4.8%, P < 0.05 and -1.7 ± 4.5% vs. 1.4 ± 4.3%, P < 0.01, respectively). These findings suggest that players with a history of injury at the upper limb joint present altered dominant upper limb proportions in comparison with the non-dominant side, and such asymmetrical proportions would appear to be specific to the location of injury. Further studies are needed to confirm the link between location of tennis injury and asymmetry in upper limb proportions using high-tech measurements in symptomatic tennis players.